INNOVATIVE APPROACHES: IMPROVING VOCABULARY ACQUISITION IN ESL CLASSROOMS IN UZBEKISTAN: INNOVATIVE APPROACHES: IMPROVING VOCABULARY ACQUISITION IN ESL CLASSROOMS IN UZBEKISTAN - Oringalieva, Dana (Журнал иностранных языков и лингвистики, 2025)
The foundation of language skill is vocabulary, which affects academic performance, writing ability, and reading comprehension. ESL students’ ability to understand and effectively communicate their ideas is greatly influenced by their strategic word acquisition as they negotiate the complexities of a new language. This conversation explores the importance of vocabulary acquisition for ESL students, looking at research results and empirical data that highlight how crucial it is to language learning, fluency, and effective integration into English-speaking contexts. A strong vocabulary is essential to the many facets of ESL learners’ journey towards linguistic competence and proficiency in the English language, from social interactions to academic success.